Biology e-learning system (SPM student) - Narayani, Kanesan (2015)
The E-learning system is an important field in the area of information communication technology for online learning. In Malaysia, the E-learning system is very popular. Traditional teaching method in secondary school causes some problems to student. Students have to bring a lot textbooks to school every day and sometime the weight goes up very heavy to carry every day. With the growing of Information and Communication Technology (ICT) in Malaysia, this situation should be changed. The Biology e-learning system can provide the solution for the above situation. There are three targeted users groups in this system which is admin, teacher and student. Firstly, admin are able to manage students and teachers record. Secondly, students are able to view their profile, update on their profile and view their result mark or study performance. They are also able to view extra notes, quiz and exercises from the system uploaded by their teachers. Thirdly, teachers are able to upload and view their student result and give comment according to their performance. Besides that, they are also able to upload extra notes, questions and exercises to the system according to subject of Biology. The entire user groups are able to take part in the interface discussion through forum especially student to student and student to teacher. Rapid Application Development (RAD) has been chosen as the methodology to develop this system which is planning, analysis design and development, testing and implementation. Adobe Dreamweaver CS5 will be used to develop this system. Security features like session registration will be implementing in this system, to make the system more secure. I believe at the end, this system could be suitable to implement in school if the SMK Sentul Convent are equipped with enough and suitable computer to run the system in order to increase the competitiveness of the school.